Agricultural growth linkages in Zimbabwe: income and equity effects - Bautista, Romeo M.; Thomas, Marcelle (International Food Policy Research Institute, 1998)
The comparative effects on GDP and household incomes associated with various pathways of agricultural growth in Zimbabwe are investigated, based on SAM (social accounting matrix) multiplier analysis. Among the five growth paths considered, the smallholder road to agricultural development yields the largest increase in national income. It benefits smallholder households the most, but the income gains to the two other low-income household groups are lower compared to those arising from the four other agricultural growth paths. Foodcrop production, in which smallholders have a dominant share, shows a larger GDP multiplier than both the traditional (tobacco and cotton) and nontraditional (horticulture)export crop sectors, which are dominated by large-scale commercial farms.